Public choice III - Mueller, Dennis C. (Cambridge University Press, 2003)
This book represents a considerable revision and expansion of Public Choice II (1989). Six new chapters have been added, and several chapters from the previous edition have been extensively revised. The discussion of empirical work in public choice has been greatly expanded. As in the previous editions, all of the major topics of public choice are covered. These include: why the state exists, voting rules, federalism, the theory of clubs, two-party and multiparty electoral systems, rent seeking, bureaucracy, interest groups, dictatorship, the size of government, voter participation, and political business cycles. Normative issues in public choice are also examined including a normative analysis of the simple majority rule, Bergson–Samuelson social welfare functions, the Arrow and Sen impossibility theorems, Rawls's social contract theory and the constitutional political economy of Buchanan and Tullock.